2 PERMANENT LINEAR-CHAINS OF SEX-CHROMOSOMES IN NEOTERMES-FULVESCENS AND KARYOTYPES OF 2 OTHER NEOTROPICAL KALOTERMITIDAE SPECIES (INSECTA, ISOPTERA) - Martins, V. G.; Mesa, A. (Natl Research Council Canada, 1995)
Meiosis and (or) mitosis of males and females of Cryptotermes brevis, Eucryptotermes wheeleri, and Neotermes fulvescens, all of them from the neotropical region, were analyzed. Cryptotermes brevis showed a similar karyotype to that obtained by other authors for specimens of the neartic and Australian regions (2n = 36 for females and 2n = 37 for males, with XX and XYY sex mechanisms, respectively). Eucryptotermes wheeleri, the only species that has been described in this genus, showed the lowest number of chromosomes reported for Isoptera (2n = 22) until now. The male meiosis of this species presents a linear chain of six sex chromosomes, three of them being X and three of them Y chromosomes. Neotermes fulvescens showed a diploid number of 40 for males and 42 for females and, in the first male meiosis, two linear chains of chromosomes, both related to sex. One of the chains, named A, presented nine chromosomes and the other, named B, seven chromosomes. Hypotheses to explain these mechanisms are formulated in this paper and putative ancestral relationships with other species of Kalotermitidae are presented.
Keywords: TERMITE; NEOTERMES; 2 LINEAR CHAINS; TRANSLOCATIONS; SOUTH AMERICAN